On Eisenstein series in M2k(Γ0(N)) and their applications - Aygin, Zafer Selcuk (2020)
Let k, N ∈ N with N square-free and k > 1. We prove an orthogonal relation and use this to compute the Fourier coefficients of the Eisenstein part of any f(z) ∈ M2k(Γ0(N)) in terms of sum of divisors function. In particular, if f(z) ∈ E2k(Γ0(N)), then the computation will to yield to an expression for the Fourier coefficients of f(z). Then we apply our main theorem to give formulas for convolution sums of the divisor function to extend the result by Ramanujan, and to eta quotients which yields to formulas for number of representations of integers by certain families of quadratic forms. At last we give essential results to derive similar results for modular forms in a more general setting.